Self-taken pharyngeal and rectal swabs are appropriate for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae in asymptomatic men who have sex with men. Issue 6 (21st November 2008) - Alexander, S; Ison, C; Parry, J; Llewellyn, C; Wayal, S; Richardson, D; Phillips, A; Smith, H; Fisher, M
Abstract : Introduction: Self-taken specimens from men who have sex with men (MSM) could be important in reducing high levels of demand on sexual health services. The performance of self-taken specimens for the detection of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) from both pharyngeal and rectal sites in asymptomatic MSM was assessed. Methods: MSM were examined according to clinic protocol: a rectal and pharyngeal swab for GC culture and a rectal swab for the CT strand displacement assay. An extra set of nurse-taken and self-taken pharyngeal and rectal specimens were also requested and were tested using the Aptima Combo 2 assay and the result compared with the routine clinic result, which was considered the gold standard. Results: A total of 272 MSM was recruited and the sensitivity and specificity of nurse-taken and patient-taken swabs, respectively, was as follows: rectal GC: 94.9% and 90.1% (nurse); 92.3% and 87.9% (patient); pharyngeal GC: 88.2% and 91.8% (nurse); 100% and 87.8% (patient); rectal CT: 80.0% and 99.6% (nurse); 91.4% and 98.2% (patient). No significant difference in sensitivity or specificity was observed between the nurse-taken and the patient-taken rectal swabs for either GC or CT. For the detection of GC from the pharynx, comparable sensitivities were achieved between nurse-taken and patient-taken swabs (p = 0.5); however, a significant difference in specificity was observed (p = 0.006). This was due to a higher number of false GC-positive self-taken pharyngeal swabs from patients with high rates (90.9%; 10/11) of confirmed concurrent GC infection in different anatomical sites. Conclusions: MSM are able to collect self-taken rectal and pharyngeal swabs that are comparable to those taken by clinicians.